The gut microbiome in lung cancer: from pathogenesis to precision therapy - Shi, Miao; Wang, Long-Fei; Hu, Wen-Tao; Liang, Zhi-Gang (Frontiers in Microbiology, 2025)
The gut microbiome has emerged as a key modulator of immune responses and treatment efficacy in oncology. Growing evidence links gut dysbiosis to resistance against immune checkpoint inhibitors (ICIs) in advanced cancers, prompting exploration of the gut-lung axis—a bidirectional network connecting intestinal microbiota with pulmonary health. Given lung cancer’s status as the leading cause of cancer mortality worldwide, understanding this axis holds significant therapeutic potential. This review synthesizes current knowledge on gut microbiota’s role in lung cancer development, diagnosis, and treatment. We highlight microbial signatures predictive of disease and therapy response, discuss microbiota-targeted interventions (e.g., probiotics, Fecal Microbiota Transplantation), and elucidate mechanistic insights into microbial-immune crosstalk. Finally, we outline future directions for leveraging the gut microbiome in personalized lung cancer management.